STRATEGIES FOR INCREASING TOURIST VISITS TO AIR BETUNG BERSERI IN SUMBER RAHAYU VILLAGE, RAMBANG SUB-DISTRICT, MUARA ENIM DISTRICT, SOUTH SUMATRA DURING THE PANDEMIC - Randi Randi; Yulasteriyani Yulasteriyani; Rizki Goffar Ismail; Yosi Arianti (Proceeding of The International Conference on Economics and Business, 2022)
Businesses run by actors in the village still have many problems such as marketing and poor facilities to tourist attractions. Air Betung Berseri tourism is located in Sumber Rahayu Village, Rambang District, Muara Enim Regency. This research focuses on Increasing the Visit of Air Betung Berseri Tourism in Sumber Rahayu Village, Rambang District, Muara Enim Regency, South Sumatra. Air Betung Berseri tourism is a superior product of Sumber Rahayu village. However, the number of visitors is only crowded at certain times. This is what causes the number of visitors to decrease day by day. The results of this research are active and social networking. The object studied here is Air Betung Berseri Tourism which is driven by actors. The actor is the manager of Air Betung Berseri Tourism. Researchers see that the strategy that must be done is to actively promote to social media and utilize the social network owned by each actor or manager of Air Betung Berseri Tourism. The research method used is qualitative research.